Aanalisis Kemampuan Melaksanakan Pembelajaran Tematik Guru Sekolah Dasar Negeri Gugus 1 Kediri, Lombok Barat - Dahlia, Kurnia Ariani; Karma, I Nyoman; Oktaviyanti, Itsna (Religion, Culture, and State Journal, 2021)
This study aims to explain the extent of the teacher’s ability to carry out thematic learning at the State Elementary School Cluster 1 Kediri, West Lombok. Thematic learning is a real challenge for teachers in carrying out classroom learning because of schools’ limited facilities and time, especially during the outbreak of the COVID-19 pandemic in Indonesia. The study applies the descriptive qualitative method. For sampling in this study, I used a non-probability technique of purposive sampling, that is, not all teachers were will become samples, but based on specific criteria. There were six teachers of the second class, State Elementary School Cluster 1 Kediri. The results of this study indicated that 1) the principle of exploring thematic learning plans in the second class of the Kediri State Elementary School has not been appropriately implemented, 2) some teachers have not been able to apply the thematic learning model fluently because learning activities constrain them carried out from home due to pandemic Covid-19, 3) learning has been carried out under the learning tools that have been prepared, 4) the principles also cannot be done because the learning process is online so that there is an evaluation interaction carried out. These data show that the implementation of thematic learning in the Kediri State of Elementary School Cluster 1 is still not well being implemented.